Does cultural heritage affect employment decisions: Empirical evidence for second generation immigrants in Germany - Anja Köbrich León (Deutsches Institut für Wirtschaftsforschung (DIW), 2013)
[Introduction ...] The remainder of the paper proceeds as follows. In the next section recent contributions to the literature are discussed shortly. The data and the empirical strategy used are described in section 3. Section 4 analyzes the results for the main measure of cultural background, namely past female LFP rates in the country of origin. Section 0 reports results for the use of alternative cultural measures as well as for the inclusion of further control variables, which were previously found to affect female labor force choices. Finally, section 6 summarizes the obtained results and discusses alternative explanations for these findings.
Keywords: 330